1998
DOI: 10.3171/jns.1998.89.2.0255
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among cerebral perfusion pressure, autoregulation, and transcranial Doppler waveform: a modeling study

Abstract: The information contained in the TCD waveform is affected by many factors, including ICP, SAP, autoregulation. and intracranial compliance. Model results indicate that only a comparative analysis of the concomitant changes in ultrasonographic quantities during multimodality monitoring may permit the assessment of several aspects of intracranial dynamics (cerebral blood flow changes, vascular pulsatility, ICP changes, intracranial compliance, CPP, and autoregulation).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(34 citation statements)
references
References 43 publications
1
30
0
3
Order By: Relevance
“…When ABP is extremely low, systolic CBF also starts to decrease and CBF pulse amplitude decreases. This prediction agrees well with the previously modeling study of Ursino et al (35), which indicates that three characteristic zones exits in the cerebral blood velocity response to reduced perfusion pressure with intact autoregulation. As shown in Fig.…”
Section: Open-loop Testingsupporting
confidence: 82%
“…When ABP is extremely low, systolic CBF also starts to decrease and CBF pulse amplitude decreases. This prediction agrees well with the previously modeling study of Ursino et al (35), which indicates that three characteristic zones exits in the cerebral blood velocity response to reduced perfusion pressure with intact autoregulation. As shown in Fig.…”
Section: Open-loop Testingsupporting
confidence: 82%
“…An increase in CVC indicates increased conductance at the pial level, to maintain CBF in the posterior region. 32 Reductions in blood flow in the posterior region of the brain may cause an interruption of the blood supply to the medulla oblongata, which contains autonomic control centers, and discrete regions responsible for consciousness. 33 An increase in PCAcvc to preferentially maintain perfusion of the cardiovascular and respiratory centers has been highlighted in response to headup tilt in AB, 22,34 and an exaggerated adaptation of this response may explain the widely reported 'remarkable tolerance to orthostatic hypotension' in the SCI population.…”
Section: Discussionmentioning
confidence: 99%
“…180 There is also a significant correlation between the cerebral perfusion pressure (CPP) and PI. 181 In a prospective study, it was shown that TCD ultrasonography is valid in predicting the patient's outcome at 6 months and correlates significantly with ICP and CPP values when it is performed within the first 24 h after severe TBI.…”
Section: Tcd and Intracranial Pressurementioning
confidence: 99%